Exultet in Material und Raum - Utz, Judith (Heidelberg University Publishing (heiUP), 2025)
Exultet iam angelica turba coelorum! – Rejoice, choirs of angels! – these words mark the beginning of the Easter Proclamation; its opening word, Exultet, gave its name to the manuscripts in which the proclamation was recorded as a central part of the Easter liturgy. The Exultet rolls, which originated between the 10th and 14th centuries, mainly in Apulia and Campania, combine writing, images and musical notation in a unique way. This book is the first to examine the material and media characteristics of the rolls from an interdisciplinary perspective, focusing not only on the objects themselves, but also on their use and perception in the Beneventan liturgy. It shows the extent to which the rolls contributed visually, aurally and olfactorily to the constitution of liturgical and social spaces.